DBMS evaluation using quantitative methods - Dasso, Aristides (2004)
Software tools evaluation and comparison is a must for users. Most of the time this is done in an incomplete an informal manner without regards for the economics involved. We present an ongoing project that evaluates different families of software using the Logic Scoring of Preference (LSP) method. This method is very briefly presented and also some of the ongoing evaluation work directed to Data Base Management Systems (DBMS) is explained.